Effects of environmental oxidant stressors on individuals with a G-6-PD deficiency with particular reference to an animal model. - Calabrese, E J (1979)
Individuals with a G-6-PD deficiency have long been known to be at increased risk to experience acute hemolysis following exposure to elevated levels of certain oxidant drugs and industrial chemicals. However, the recognition of enhanced susceptibility to environmental (or ambient) pollutants has generally not been considered. Recent theoretical studies have suggested that elevated levels of ambient ozone may be an etiologic factor in the onset of acute hemolysis in the G-6-PD deficient individual. Furthermore, the proposed usage of either chloramines or chlorine dioxide as replacements for chlorine for the disinfection of drinking water should be investigated with respect to their potential adverse effects of individuals at increased risk to oxidant stressors. In order to test these theoretical associations, two mouse strains, one with low and the other with high levels of G-6-PD activity in their red blood cells are being investigated to determine if they simulate human G-6-PD deficient and normal individuals, respectively. Preliminary results indicate that the mouse strain with low G-6-PD activity is markedly more susceptible to sodium chlorite than mice of the high G-6-PD strain. This differential susceptibility to sodium chlorite toxicity between the high and low G-6-PD mouse strains suggests that further research designed to validate the efficacy of this mouse model as a predictor of the human situation is warranted.